Cancellation of Regional Regulations in Indonesian: An Overview of the Conception of Constitutional Democracy - Muhammad Mutawalli; Andi Tenri Yeyeng; Piaget Mpoto Balebo; Lourenco de Deus Mau Lulo (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2023)
In connection with the decision of the Constitutional Court Number 137/PUU-XIII/2015, this study examined the cancellation of regional regulations reviewed in Indonesia's constitutional system. The research method is normative legal research, or looking at the laws and regulations that are in effect. This study also collects legal materials using the library method, which are presented qualitatively and descriptively. This study will demonstrate the connection between the cancellation of regional regulations and the authority and position of the Minister of Home Affairs as assistant to the president in the Indonesian constitutional system. The regional regulation was scrapped because it was thought to make it harder to make investments in Indonesia. The Republic of Indonesia's central government has the authority to oversee the administration of regional governments, overseeing every regional regulation and regional head regulation. Be that as it may, after the choice of the Protected Court, the Clergyman and lead representative as delegates of the focal government never again have the position to drop a territorial guideline. In conclusion, this study reveals that the governor and the Ministry of Home Affairs can only cancel regional regulations that conflict with higher regulations, are not in line with interests, or violate moral norms in general through the process of testing regional regulations before they are enacted (executive). preview). This is different from the situation before the Constitutional Court's decision, when the Minister of Home Affairs and the Governor still held authority.